Differential expression of secreted factors SOSTDC1 and ADAMTS8 cause profibrotic changes in linear morphoea fibroblasts. (6th January 2019) - Badshah, I.I.; Brown, S.; Weibel, L.; Rose, A.; Way, B.; Sebire, N.; Inman, G.; Harper, J.; O'Shaughnessy, R.F.L.
Summary: Background: Linear morphoea (LM) is a rare connective tissue disorder characterized by a line of thickened skin and subcutaneous tissue and can also affect the underlying muscle and bone. Little is known about the disease aetiology, with treatment currently limited to immune suppression, and disease recurrence post‐treatment is common. Objectives: In order to uncover new therapeutic avenues, the cell‐intrinsic changes in LM fibroblasts compared with site‐matched controls were characterized. Methods: We grew fibroblasts from site‐matched affected and unaffected regions from five patients with LM, we subjected them to gene expression analysis and investigation of SMAD signalling. Results: Fibroblasts from LM lesions showed increased migration, proliferation, altered collagen processing, and abnormally high basal levels of phosphorylated SMAD2, thereby rendering them less responsive to transforming growth factor (TGF)‐β1 and reducing the degree of myofibroblast differentiation, which is a key component of the wound‐healing and scarring process in normal skin. Conditioned media from normal fibroblasts could reverse LM‐affected fibroblast migration and proliferation, suggesting that the LM phenotype is driven by an altered secretome. Gene array analysis and RNA‐Seq indicated upregulation of ADAMTS8 and downregulation of FRAS1 and SOSTDC1 . SOSTDC1 knock‐down recapitulated the reduced TGF‐β1 responsiveness and LM fibroblast migration, while overexpression of ADAMTS8 induced myofibroblast markers. Conclusions: We demonstrate that cell‐intrinsic changes in the LM fibroblast secretome lead to changes observed in the disease, and that secretome modulation could be a viable therapeutic approach in the treatment of LM. Abstract : What's already known about this topic? Linear morphoea (LM) is a rare connective tissue disorder. The underlying mechanism responsible for the fibrosis of LM is unknown. What does this study add? LM fibroblasts from diseased skin possess a persistent identifiable cell phenotype. LM fibroblasts display increased cell growth and migration, and reduced response to transforming growth factor‐β1. What is the translational message? Cell‐intrinsic changes in the LM fibroblast secretome lead to changes observed in the disease. Secretome modulation could be a viable therapeutic approach in the treatment of LM. Linked Comment:  Mellody et al. Br J Dermatol 2019; 180 :985–987 . Respond to this article